トウブ ナンキョク タイリク リュツォ・ホルムワン トウガン ノ ドジョウ カラ ブンリ サレタ ケンキセイ キン CLOSTRIDIA - 三和, 敏夫; ミワ, トシオ; MIWA, Toshio (国立極地研究所, 1975)
P(論文) From the soil (permafrost, moraine, penguins' rookery, lake, coast, etc.) collected in the area around Syowa Station, the Antarctica during 1972-1973, 150 strains of Clostridium were isolated and identified according to the VPI manual. 1) C. perfringens (28%), C. sordellii (22%), C. bifermentans (23%), C. sporogenes (4%), C. plagarum (3%), C. paraperfringens (2%), C. septicum (1%) and C. tertium (1%) were the principal species found, but 17% of strains remained unidentified. 2) Soil samples from places where contamination by men and animals is scarce were found to contain Clostridia. 3) Strains of C. sordellii were isolated from samples of many places. Eighty-five percent (85%) of them were obtained from the same soil samples from which strains of C. bifermentans were isolated also. 4) Biological properties of C. sordellii isolated agreed almost completely with those of C. bifermentans except the urease reaction. 5) All strains of Clostridia were isolated from the Antarctic soil could not survive the heating at 80℃ for 10 minutes. departmental bulletin paper